Features of Immunosenescence in Women Newly Diagnosed With Breast Cancer - Trintinaglia, Lauren; Bandinelli, Lucas Poitevin; Grassi-Oliveira, Rodrigo; Petersen, Laura Esteves; Anzolin, Marcelo; Correa, Bruna Luz; Schuch, Jaqueline Bohrer; Bauer, Moisés Evandro (Frontiers in Immunology, 2018)
Adults exposed to childhood maltreatment have increased stress reactivity. This profile is associated with dysregulation of the immune system, including enhanced inflammatory reactions and premature senescence. Subjects exposed to early-life stress have increased risk for several age-related diseases, including cardiovascular disease, type II diabetes and cancer. Although previous studies have reported immune changes in advanced cancer, very little information is available regarding early stage breast cancer. Here, twenty-nine patients with breast cancer were recruited: 15 with history of childhood maltreatment (CM+) and 14 without history (CM-). Twenty-seven healthy women without CM were selected as the control group. Peripheral blood was collected and lymphocyte subsets phenotyped by multi-color flow cytometry (B cells, CD4+ T, CD8+ T, natural killer (NK) cells, activated T cells, regulatory T cells, and senescence-associated T cells). Because human cytomegalovirus (CMV) was associated with premature immunosenescence, the CMV serology was determined by ELISA. None of the subjects had IgM reactivity to CMV, excluding acute viral infection. There was a higher proportion of patients with increased CMV IgG levels in the CM+ group as compared to CM- or controls. After adjusting for age and education, early-differentiated T cells (CD27+CD28+) were found reduced in CM+ and CM– patients (p <0.0001). In contrast, intermediate-differentiated T cells (CD27-CD28+; p<0.0001), senescent T cells (CD27-CD28-; p<0.0001) and exhausted T cells (CD8+CD27-CD28-PD1+; p<0.0001) were found expanded in both CM+ and CM– groups. Our data suggest that premature immunosenescence is associated with newly diagnosed breast cancer, regardless of the CM history.